Mathematical law of cardiac dynamic systems: reduction of its evaluation time to 18 hours - Rodríguez Velásquez, Javier Oswaldo; Correa Herrera, Sandra Catalina; Pizano, Alejandro; Ronderos, Miguel Alberto; Prieto Bohórquez, Signed Esperanza; Godoy, Carol; Rojas, Juan Alexander; Benitez, Juan; Rodríguez Correa, Dharma; Avilan, Eliana (Revista de la Facultad de Ciencias Medicas (Cordoba, Argentina), 2021)
Previously, a physical-mathematical law was developed for the evaluation of continuous electrocardiographic and Holter registers, with which all cardiac attractors were deduced and normality, pathological states and evolution between states were differentiated. There were taken 200 cardiac dynamics, 150 with different types of cardiac pathologies and 50 normal ones, to which the exponential law was applied in 18 and 21 hours. For this, a sequence of heart rates was simulated, with which the chaotic attractor was constructed. Next, the mathematical diagnosis was determined with the law based on the spatial occupation of the attractor, and the fractal dimension was calculated. Finally, statistical validation of the mathematical method in 18 hours was performed against the Gold Standard. Subjects with normal chaotic cardiac dynamics presented values in the Kp grid between 205 and 384, whereas subjects with pathological dynamics presented values between 61 and 191 in 18 hours. The evaluation of the concordance between the mathematical diagnosis in 18 hours and the conventional evaluation, taken as Gold Standard resulted in sensitivity and specificity values of 100% and a Kappa coefficient of 1. It was confirmed the clinical capacity of the law to diagnose objectively and with reproducibility in 18 hours.